Core-Level Spectroscopy of Photoactive Materials - Hart, Jack (2023)
In order for next generation solar technologies to continue to improve, detailed chemical and electronic information is essential. Core-level spectroscopies, such as X-ray photoelectron spectroscopy, X-ray absorption spectroscopy, and resonant photoelectron and Auger spectroscopies are capable of providing this information. These techniques have been used for decades across many systems but are limited to ultra-high vacuum pressures, however more recently measurements at ambient pressures have become possible. The thesis presented herein applies core-level spectroscopies to two systems: dye sensitised solar cells and solar water splitting. In the former, ultra-high vacuum core-level spectroscopies are employed to probe the chemical and electronic coupling between the dye and substrate. For the latter, ambient-pressure X-ray photoelectron spectroscopy allows the oxidation of a potential solar water splitting catalyst to be monitored.